Child survival: the role of a mother's education. Issue 11 (November 2022) - Amoah, Anthony; Asamoah, Moses Kumi
Abstract: In developing countries, children are considered as social and human capital needed for growth and development. However, the ability of uneducated parents to provide basic services to keep a child alive has always been in doubt. This has resulted in the avoidable deaths of children. This study seeks to examine the role of a mother's education in keeping a child alive. This is achieved by using the Ghana Demographic and Health Survey (DHS) Dataset (1988–2014) with 33, 896 observations. This study uses the negative binomial model and finds an inverse and statistically highly significant relationship between a mother's education and the survival of her child in Ghana. Further robustness checks confirm that the result is consistent across gender of child and years of data collection. In line with the finding, this study recommends women's education from the basic education level as it drives the probability of saving a life. Globally, we suggest that education, especially at the basic level, should include health education to address numerous health concerns. Abstract : Child survival; Child mortality; Education, Mother education; Mother empowerment; Maternal education.